PEMETAAN GEOMORFOLOGI TERUMBU KARANG PULAU TUNDA MENGGUNAKAN KLASIFIKASI BERBASIS OBJEK - Fahriansyah Fahriansyah; Jonson Lumban Gaol; James P Panjaitan (Fakultas Perikanan dan Ilmu Kelautan, 2017)
Mapping of coral reefs geomorphic in Tunda Island has not been done before using an object-based image classification. This mapping can be used as the basic of information to planning and area development towards the optimum utilization such as marine ecotourism area. This study aims to mapping coral reef geomorphic zone of Tunda Island using object base classification. Data analysis using multispectral image Worldview-2 with data acquisition of August 25, 2013 and bathymetric profiles. The classification using of multiresolution segmentation. The classification is divided into two levels of classification. Level 1 segmentation using parameter of scale 200, shape 0.6 and compactness 0.4. Level 2 Segmentation using parameter of scale 30, shape 0.6 and compactness 0.4. The classification object segmentation able to produce a map with high accuracy at every level. The classification accuracy of Level 1 is 97% and level 2 is 91%.